Polyamide acid composition, method for producing polyimide, method for producing laminate, and method for producing electronic device
By using a composition of specific polyamic acid and a high-safe organic solvent, the problems of poor adhesion and increased internal stress in electronic devices are solved, and better performance of electronic devices and stability.
Patent Information
- Application Number
- CN202380049001.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-08
- Publication Date
- 2025-02-14
AI Technical Summary
After the conventional polyamic acid composition is applied to the support and imidized, it is prone to poor adhesion and increased internal stress, which affects the performance of electronic devices.
By using a composition containing a specific polyamic acid and an organic solvent with higher safety, the generation of poor adhesion is inhibited and internal stress is reduced by adjusting the chemical structure of the polyamic acid and the selection of solvents.
It effectively suppresses poor adhesion between the polyimide film and the support, reduces internal stress, and improves the performance and stability of electronic devices.
Smart Images

Figure CN119452037A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polyamic acid composition, a method for producing a polyimide, a method for producing a laminate, and a method for producing an electronic device. The present invention further relates to an electronic device material using polyimide, a thin film transistor (TFT) substrate, a flexible display substrate, a color filter, a printed matter, an optical material, an image display device (more specifically, a liquid crystal display device, an organic EL (Electroluminescence), an electronic paper, etc.), a 3D display, a solar cell, a touch panel, a transparent conductive film substrate, and an alternative material for components currently using glass. Background Art
[0002] With the rapid development of electronic devices such as liquid crystal displays, organic EL, electronic paper, solar cells, touch panels, etc., the devices are becoming thinner, lighter, and more flexible. In these devices, polyimide is used as a substrate material instead of a glass substrate.
[0003] In these devices, various electronic components, such as thin film transistors or transparent electrodes, are formed on the substrate, and the formation of these electronic components requires high temperature processes. Polyimide has sufficient heat resistance to adapt to high temperature processes, and its thermal expansion coefficient (CTE) is close to that of glass substrates and electronic components, so it is not easy to generate internal stress, and is suitable for use as a substrate material for flexible displays, etc.
[0004] The above-mentioned substrate material can be produced by applying a solution in which polyamic acid is dissolved (polyamic acid composition) on a support, imidizing the polyamic acid to form a polyimide film, and further laminating an electronic element thereon.
[0005] As a solvent for dissolving polyamic acid, an amide solvent having a relatively small number of carbon atoms, such as N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and N,N-dimethylacetamide (DMAC), is generally used. However, from the viewpoint of the impact on the environment and the human body, a change to a safer solvent is gradually required.
[0006] As a preparation example of a polyamic acid composition using a safer solvent, it is known that water is used as a solvent by utilizing polyamic acid salt (Patent Document 1, etc.). In addition, it is known that an example of synthesizing polyamic acid using alkoxy-N-substituted propionamide as a solvent with lower concerns about teratogenicity (Patent Document 2 and Patent Document 3, etc.) is used.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2012-36382
[0010] Patent Document 2: Japanese Patent Application No. 2017-517582
[0011] Patent Document 3: International Publication No. 2022 / 054850 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] The inventors of the present invention have verified that if the polyamic acid composition described in patent documents 1 to 3 is applied to a support and polyamic acid is imidized, poor adhesion is easily produced between the obtained polyimide film and the support, and the internal stress generated at the interface of the polyimide film and the support becomes larger. Hereinafter, the poor adhesion between the polyimide film and the support is sometimes referred to as "poor adhesion". In addition, the internal stress generated at the interface of the polyimide film and the support is sometimes referred to as "internal stress". If the internal stress becomes larger, there is a possibility that it is difficult to be applied to electronic devices.
[0014] The present invention has been completed in view of the above-mentioned actual situation, and its purpose is to provide a polyamic acid composition that can not only use a safer solvent and suppress the occurrence of poor adhesion, but also reduce internal stress, as well as a method for producing a polyimide using the polyamic acid composition, a method for producing a laminate, and a method for producing an electronic device.
[0015] Solutions for solving problems
[0016] <Methods of the present invention>.
[0017] The present invention includes the following aspects.
[0018] [1] A polyamic acid composition comprising polyamic acid and an organic solvent,
[0019] The polyamic acid has a residue containing a divalent organic group represented by the following chemical formula (1), a 3,3',4,4'-biphenyltetracarboxylic dianhydride residue, and a p-phenylenediamine residue.
[0020] The organic solvent includes one or more compounds selected from the group consisting of compounds represented by the following general formula (2) and compounds represented by the following general formula (3).
[0021]
[0022] In the above general formula (2), R 1 , R 2 and R 3Each independently represents a hydrogen atom or a monovalent organic group having 1 or more carbon atoms, and R 1 , R 2 and R 3 At least one of represents a monovalent organic group having 2 or more carbon atoms,
[0023] In the above general formula (3), R 4 It represents a monovalent organic group having 2 or more carbon atoms.
[0024] [2] The polyamic acid composition according to [1], wherein the residue containing the divalent organic group represented by the chemical formula (1) is one or more residues selected from the group consisting of a tetravalent organic group represented by the following chemical formula (4), a tetravalent organic group represented by the following chemical formula (5), and a divalent organic group represented by the following chemical formula (6).
[0025]
[0026] [3] The polyamic acid composition according to [1] or [2], wherein the content of the residue containing the divalent organic group represented by the chemical formula (1) is 15 mol% or less relative to 100 mol% of the total of all tetracarboxylic dianhydride residues constituting the polyamic acid and all diamine residues constituting the polyamic acid.
[0027] [4] The polyamic acid composition according to any one of [1] to [3], wherein the organic solvent is 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide or 1-butyl-2-pyrrolidone.
[0028] [5] The polyamic acid composition according to any one of [1] to [4], wherein the polyamic acid further has a 1,3-bis(3-aminopropyl)tetramethyldisiloxane residue.
[0029] [6] The polyamic acid composition according to [5], wherein the content of the 1,3-bis(3-aminopropyl)tetramethyldisiloxane residue is 0.1 mol % or more and 1.0 mol % or less relative to the total amount of diamine residues constituting the polyamic acid.
[0030] [7] The polyamic acid composition according to any one of [1] to [6], further comprising a silane coupling agent.
[0031] [8] A method for producing a polyimide, comprising heating the polyamic acid composition according to any one of [1] to [7] to imidize the polyamic acid.
[0032] [9] A method for producing a laminate, the laminate comprising a support and a polyimide film,
[0033] In the above method, the polyamic acid composition described in any one of [1] to [7] is applied onto a support to form a coating film containing the polyamic acid, and the coating film is heated to imidize the polyamic acid.
[0034]
[10] A method for manufacturing an electronic device, comprising:
[0035] A step Sa of heating the polyamic acid composition according to any one of [1] to [7] to imidize the polyamic acid; and
[0036] Step Sb is to arrange electronic components on the polyimide film obtained in the above step Sa.
[0037] Effects of the Invention
[0038] According to the present invention, there can be provided a polyamic acid composition that can use a safer solvent, suppress the occurrence of poor adhesion, and reduce internal stress, as well as a method for producing a polyimide, a method for producing a laminate, and a method for producing an electronic device using the polyamic acid composition. DETAILED DESCRIPTION
[0039] Hereinafter, preferred embodiments of the present invention will be described in detail, but the present invention is not limited thereto. In addition, all academic documents and patent documents described in this specification are incorporated into this specification as references.
[0040] First, the terms used in this specification are explained. "Constitutional unit" refers to a repeating unit constituting a polymer. "Polyamic acid" is a polymer containing a structural unit represented by the following general formula (7) (hereinafter, sometimes described as "structural unit (7)").
[0041]
[0042] In the general formula (7), A 1 represents a tetracarboxylic dianhydride residue (a tetravalent organic group derived from tetracarboxylic dianhydride), A 2 It represents a diamine residue (a divalent organic group derived from a diamine).
[0043] The content of the structural unit (7) relative to all the structural units constituting the polyamic acid is, for example, 50 mol% to 100 mol%, preferably 60 mol% to 100 mol%, more preferably 70 mol% to 100 mol%, further preferably 80 mol% to 100 mol%, further more preferably 90 mol% to 100 mol%, and may be 100 mol%.
[0044] The "1% weight loss temperature" refers to the temperature at which the weight of the polyimide at a measurement temperature of 150° C. is reduced by 1% relative to the weight of the reference (100% by weight). The 1% weight loss temperature is measured by the same method as in the following Examples or a method based thereon.
[0045] Both "alkyl" and "alkoxyalkyl" are linear or branched and unsubstituted.
[0046] Hereinafter, "system" is sometimes added after the compound name to collectively refer to the compound and its derivatives. In addition, when "system" is added after the compound name to indicate the polymer name, if there is no provision, it means that the repeating unit of the polymer is derived from the compound or its derivative. In addition, tetracarboxylic dianhydride is sometimes recorded as "acid dianhydride". In addition, the components, functional groups, etc. exemplified in this specification may be used alone or in combination of two or more unless otherwise specified.
[0047] <Preferred embodiment of the present invention>
[0048] The polyamic acid composition of the present embodiment includes polyamic acid and an organic solvent. The polyamic acid (hereinafter, sometimes referred to as "specific polyamic acid") included in the polyamic acid composition of the present embodiment has a residue of a divalent organic group represented by the following chemical formula (1) (hereinafter, sometimes referred to as "residue (1)"), a 3,3',4,4'-biphenyltetracarboxylic dianhydride residue, and a p-phenylenediamine residue. The organic solvent included in the polyamic acid composition of the present embodiment includes one or more compounds selected from the group consisting of a compound represented by the following general formula (2) (hereinafter, sometimes referred to as "compound (2)") and a compound represented by the following general formula (3) (hereinafter, sometimes referred to as "compound (3)"). Hereinafter, one or more compounds (organic solvents) selected from the group consisting of compound (2) and compound (3) are sometimes referred to as "specific organic solvents". In addition, 3,3',4,4'-biphenyltetracarboxylic dianhydride is sometimes referred to as "BPDA". In addition, p-phenylenediamine is sometimes referred to as "PDA".
[0049]
[0050] In the general formula (2), R 1 , R 2and R 3 Each independently represents a hydrogen atom or a monovalent organic group having 1 or more carbon atoms, and R 1 , R 2 and R 3 At least one of represents a monovalent organic group having 2 or more carbon atoms. 4 It represents a monovalent organic group having 2 or more carbon atoms.
[0051] Generally speaking, in polyamic acid compositions, amide solvents with relatively small carbon atoms such as N,N-dimethylformamide, N-methyl-2-pyrrolidone, and N,N-dimethylacetamide are used from the viewpoint of improving solubility and properties, but people have gradually realized that these solvents are harmful to health. In contrast, specific organic solvents have less impact on the environment or human body and are safer.
[0052] In order to improve safety, R in the general formula (2) 1 , R 2 and R 3 , are each independently preferably a monovalent organic group having 1 or more carbon atoms, and more preferably a monovalent organic group having 1 or more carbon atoms and 6 or less carbon atoms. In order to further improve safety, R in the general formula (2) 1 and R 2 , are each independently preferably an alkyl group having 1 or more carbon atoms, and more preferably an alkyl group having 1 or more carbon atoms and 6 or less carbon atoms. In order to further improve safety, R in the general formula (2) 3 , preferably an alkoxyalkyl group having 2 or more carbon atoms, more preferably an alkoxyalkyl group having 2 or more and 6 or less carbon atoms.
[0053] In order to improve safety, R in the general formula (3) 4 , preferably a monovalent organic group having 2 to 6 carbon atoms. In order to further improve safety, R in the general formula (3) 4 , preferably an alkyl group having 2 to 6 carbon atoms.
[0054] Examples of compound (2) include 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, N,N-diethylacetamide, and N,N-dimethylpropionamide. Among these, 3-methoxy-N,N-dimethylpropionamide and 3-butoxy-N,N-dimethylpropionamide are preferred from the viewpoint of safety.
[0055] Examples of the compound (3) include 1-ethyl-2-pyrrolidone and 1-butyl-2-pyrrolidone. Among these, 1-butyl-2-pyrrolidone is preferred from the viewpoint of safety.
[0056] The polyamic acid composition of the present embodiment may contain only compound (2) as a specific organic solvent, may contain only compound (3) as a specific organic solvent, or may contain both compound (2) and compound (3) as specific organic solvents. In order to improve safety, the specific organic solvent is preferably 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide or 1-butyl-2-pyrrolidone, and more preferably 3-methoxy-N,N-dimethylpropionamide or 1-butyl-2-pyrrolidone.
[0057] The specific polyamic acid contains a BPDA residue and a PDA residue, and thus has a rigid structure. Therefore, the specific polyamic acid can reduce internal stress.
[0058] On the other hand, according to the research of the inventors, it has been found that if a polyamic acid composition comprising a polyamic acid and a specific organic solvent with a rigid structure is used to manufacture polyimide film, it becomes easy to produce floating at the interface of polyimide film and support. If there is floating at the interface of polyimide film and support, there is a worry that the yield rate decreases when polyimide film is peeled off in the formation of electronic components or when the polyimide film is peeled off from the support after forming the electronic components. It should be noted that so-called "floating" refers to the state of poor adhesion between polyimide film and other material layers (more specifically, glass substrate, sacrificial layer, etc.) caused by the secondary component or residual solvent produced when imidization. As specific "floating", it can be cited as follows: the state of polyimide film floating from the support, the state of interlayer peeling between polyimide film and other material layers produced by a part of polyimide film being destroyed, etc.
[0059] Generally speaking, the molecular chains of the polyimide film obtained by the polyamic acid with BPDA residue and PDA residue are closely stacked, so if a relatively large solvent with carbon number such as a specific organic solvent is used, a trend of deterioration of exhaust properties is presented. Therefore, it is inferred that in the process of applying the polyamic acid composition of the polyamic acid comprising a rigid structure on a support and imidizing, the remaining solvent and the detached molecules produced by imidization are enclosed, so that it is easy to float at the interface of the polyimide film and the support. To this, the inventors have conducted in-depth research, and the results show that if the polyamic acid (specific polyamic acid) with BPDA residue and PDA residue and residue (1) is used, good exhaust properties can be achieved by the large volume structure of residue (1), and internal stress can be reduced. That is, according to the polyamic acid composition of the present embodiment, owing to comprising specific polyamic acid and specific organic solvent, a solvent with higher safety can be used and the generation of poor adhesion can be suppressed by good exhaust properties, and internal stress can be reduced.
[0060] The residue (1) is a residue contained in the polyamic acid, and is therefore one or more residues selected from the group consisting of tetracarboxylic dianhydride residues and diamine residues. The specific polyamic acid may have only a tetracarboxylic dianhydride residue as the residue (1), may have only a diamine residue as the residue (1), or may have both a tetracarboxylic dianhydride residue and a diamine residue as the residue (1).
[0061] Examples of the tetracarboxylic dianhydride used to form the residue (1) include spiro[11H-difuro[3,4-b:3',4'-i]xanthene-11,9'-[9H]fluorene]-1,3,7,9-tetraone (hereinafter, sometimes referred to as "SFDA"), 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride (hereinafter, sometimes referred to as "BPAF"), 9,9-bis[4-(3,4-dicarboxyphenoxy)phenyl]fluorene dianhydride, 5,5'-[9H-fluorene-9 -ylidenebis(2-methyl-4,1-phenylene)]bis(1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylate), N,N'-(9H-fluorene-9-ylidenedi-4,1-phenylene)bis[1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxamide], 5,5'-spiro[9H-fluorene-9,9'-[9H]xanthene]-3',6'-diylbis(1,3-dihydro-1,3-dioxo-5-isobenzofurancarboxylate), etc. In order to further suppress the occurrence of poor adhesion, the tetracarboxylic dianhydride used to form the residue (1) is preferably SFDA or BPAF.
[0062] Examples of the diamine used to form the residue (1) include 9,9-bis(4-aminophenyl)fluorene (hereinafter, sometimes referred to as "BAFL"), 3,3'-(9H-fluorene-9,9-diyl)diphenylamine, and 4,4'-(9H-fluorene-9-ylidene)bis[2-fluoroaniline]. In order to further suppress the occurrence of poor adhesion, the diamine used to form the residue (1) is preferably BAFL.
[0063] In order to further suppress the occurrence of poor adhesion, the residue (1) is preferably one or more residues selected from the group consisting of SFDA residues, BPAF residues and BAFL residues. The SFDA residue is a tetravalent organic group represented by the following chemical formula (4). The BPAF residue is a tetravalent organic group represented by the following chemical formula (5). The BAFL residue is a divalent organic group represented by the following chemical formula (6).
[0064]
[0065] Among them, the SFDA residue has a rigid structure derived from the xanthene structure. Therefore, in order to further reduce the internal stress and further suppress the occurrence of poor adhesion, the SFDA residue is particularly preferred as the residue (1).
[0066] In order to suppress the increase of the thermal expansion coefficient, the content of the residue (1) is preferably 15 mol% or less, more preferably 10 mol% or less, and may be 5 mol% or less, relative to the total of 100 mol% of all tetracarboxylic dianhydride residues constituting the specific polyamic acid and all diamine residues constituting the specific polyamic acid (when a plurality of residues (1) are included, their total content), and in order to further suppress the occurrence of poor adhesion, the content of the residue (1) is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more, relative to the total of 100 mol% of all tetracarboxylic dianhydride residues constituting the specific polyamic acid and all diamine residues constituting the specific polyamic acid (when a plurality of residues (1) are included, their total content), and may be 0.1 mol% or more, more preferably 0.5 mol% or more, and further preferably 1 mol% or more.
[0067] When synthesizing the specific polyamic acid, an acid dianhydride other than BPDA and the acid dianhydride used to form the residue (1) may be used as a monomer within a range that does not impair its performance. Examples of the acid dianhydride other than BPDA and the acid dianhydride used to form the residue (1) include pyromellitic acid dianhydride, p-phenylene trimellitic acid dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 2,2',3,3'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 4,4'-oxydiphthalic acid anhydride, and bicyclo[1,2,5,6-naphthalenetetracarboxylic acid dianhydride. Hexyl-3,3',4,4'-tetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 2'-oxodispiro[bicyclo[2.2.1]heptane-2,1'-cyclopentane-3',2"-bicyclo[2.2.1]heptane]-5,6:5",6"-tetracarboxylic dianhydride and derivatives thereof may be used alone or in combination of two or more.
[0068] In order to further reduce the internal stress, the content of the BPDA residue is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, and may be 100 mol% based on the total amount (100 mol%) of the tetracarboxylic dianhydride residues constituting the specific polyamic acid.
[0069] When the residue (1) is a residue derived from an acid dianhydride (SFDA residue, BPAF residue, etc.), in order to further suppress the occurrence of poor adhesion, the content of the residue (1) is preferably 0.1 mol% or more, and more preferably 0.5 mol% or more, relative to the total amount (100 mol%) of the tetracarboxylic dianhydride residues constituting the specific polyamic acid. In addition, when the residue (1) is a residue derived from an acid dianhydride (SFDA residue, BPAF residue, etc.), in order to further reduce the internal stress, the content of the residue (1) is preferably 10 mol% or less, and more preferably 8 mol% or less, relative to the total amount (100 mol%) of the tetracarboxylic dianhydride residues constituting the specific polyamic acid.
[0070] In order to further suppress the occurrence of poor adhesion and further reduce internal stress, the total content of the tetracarboxylic dianhydride residues constituting the specific polyamic acid (100 mol%) is preferably 60 mol% or more, and the total content of the residues (1) derived from the acid dianhydride and the BPDA residues is more preferably 70 mol% or more, further preferably 80 mol% or more, particularly preferably 90 mol% or more, and may be 100 mol%.
[0071] When synthesizing a specific polyamic acid, diamines other than PDA and the diamine used to form the residue (1) may be used as monomers within a range that does not impair its performance. Examples of diamines other than PDA and the diamine used to form the residue (1) include: 4-aminophenyl 4-aminobenzoate, 2,2'-bis(trifluoromethyl)-4,4'-diaminodiphenyl ether, 1,4-cyclohexanediamine, 4,4'-diaminobenzanilide, metaphenylenediamine, 4,4'-oxydiphenylamine, 3,4'-oxydiphenylamine, N,N'-bis(4-aminophenyl)terephthalamide, 4,4'-diaminodiphenyl sulfone, metaphenylenediamine, Toluidine, o-tolidine, 4,4'-bis(4-aminophenoxy)biphenyl, 2-(4-aminophenyl)-6-aminobenzoxazole, 3,5-diaminobenzoic acid, 4,4'-diamino-3,3'-dihydroxybiphenyl, 4,4'-methylenebis(cyclohexylamine), 1,3-bis(3-aminopropyl)tetramethyldisiloxane (hereinafter, sometimes referred to as "PAM-E") and derivatives thereof, which may be used alone or in combination of two or more.
[0072] In order to improve the adhesion between the polyimide film and the support, the diamine other than PDA and the diamine for forming the residue (1) is preferably PAM-E. That is, in order to improve the adhesion between the polyimide film and the support, the specific polyamic acid preferably has a PAM-E residue.
[0073] In order to further improve the adhesion between the polyimide film and the support, the content of the PAM-E residue is preferably 0.05 mol% or more, more preferably 0.1 mol% or more, and also 0.2 mol% or more, relative to the total amount (100 mol%) of the diamine residues constituting the specific polyamic acid. In addition, in order to suppress the decrease in the yield when the polyimide film is peeled off from the support after forming the electronic component, the content of the PAM-E residue is preferably 1.0 mol% or less, more preferably 0.9 mol% or less, further preferably 0.8 mol% or less, further more preferably 0.7 mol% or less, and also 0.6 mol% or less, relative to the total amount (100 mol%) of the diamine residues constituting the specific polyamic acid.
[0074] In order to further reduce the internal stress, the content of the PDA residue is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, and may be 100 mol% relative to the total amount (100 mol%) of the diamine residues constituting the specific polyamic acid.
[0075] When the residue (1) is a residue derived from a diamine (such as a BAFL residue), in order to further suppress the occurrence of poor adhesion, the content of the residue (1) is preferably 0.1 mol% or more, and more preferably 0.5 mol% or more, relative to the total amount (100 mol%) of the diamine residues constituting the specific polyamic acid. In addition, when the residue (1) is a residue derived from a diamine (such as a BAFL residue), in order to further reduce the internal stress, the content of the residue (1) is preferably 10 mol% or less, more preferably 8 mol% or less, and even more preferably 5 mol% or less, relative to the total amount (100 mol%) of the diamine residues constituting the specific polyamic acid.
[0076] In order to further suppress the occurrence of poor adhesion and further reduce internal stress, the total content of the residue (1) derived from the diamine and the PDA residue is preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, particularly preferably 90 mol% or more, and may be 100 mol% relative to the total amount (100 mol%) of the diamine residues constituting the specific polyamic acid.
[0077] In the case where the specific polyamic acid has a PAM-E residue, in order to obtain a polyamic acid composition that can further suppress the occurrence of poor adhesion, further reduce internal stress, and further improve the adhesion between the polyimide film and the support, the total content of the PAM-E residue, the residue (1) derived from the diamine, and the PDA residue is preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, particularly preferably 90 mol% or more, and may also be 100 mol%.
[0078] In order to further reduce the internal stress and further suppress the occurrence of poor adhesion, the specific polyamic acid preferably satisfies the following condition 1, more preferably satisfies the following condition 2, further preferably satisfies the following condition 3, and particularly preferably satisfies the following condition 4.
[0079] Condition 1: The total content of the residue (1), the BPDA residue, and the PDA residue is 90 mol% or more relative to 100 mol% of the total of all tetracarboxylic dianhydride residues constituting the specific polyamic acid and all diamine residues constituting the specific polyamic acid.
[0080] Condition 2: The above condition 1 is satisfied and the compound also has a PAM-E residue.
[0081] Condition 3: The above-mentioned condition 2 is satisfied, and the content of the PAM-E residue is 0.1 mol% or more and 1.0 mol% or less relative to the total amount (100 mol%) of the diamine residues constituting the specific polyamic acid.
[0082] Condition 4: The above-mentioned condition 3 is satisfied, and the total content of residue (1), BPDA residue, PDA residue and PAM-E residue is 95 mol% or more and 100 mol% or less relative to the total of 100 mol% of all tetracarboxylic dianhydride residues constituting the specific polyamic acid and all diamine residues constituting the specific polyamic acid.
[0083] The specific polyamic acid can be synthesized by a known general method, for example, by reacting a diamine with a tetracarboxylic dianhydride in an organic solvent. An example of a specific synthesis method of the specific polyamic acid is described. First, in an inert gas atmosphere such as argon or nitrogen, a diamine is dissolved or dispersed in an organic solvent in a slurry form to prepare a diamine solution. Then, the tetracarboxylic dianhydride is added to the above-mentioned diamine solution after being dissolved or dispersed in an organic solvent in a slurry form, or in a solid state.
[0084] In the case of using diamine and tetracarboxylic dianhydride to synthesize a specific polyamic acid, by adjusting the amount of diamine substance (when using multiple diamines, the amount of each diamine substance) and the amount of tetracarboxylic dianhydride substance (when using multiple tetracarboxylic dianhydrides, the amount of each tetracarboxylic dianhydride substance), the desired specific polyamic acid (polymer of diamine and tetracarboxylic dianhydride) can be obtained. The molar fraction of each residue in the specific polyamic acid is consistent with the molar fraction of each monomer (diamine and tetracarboxylic dianhydride) used in the synthesis of polyamic acid. In addition, by blending two polyamic acids, a specific polyamic acid containing multiple tetracarboxylic dianhydride residues and multiple diamine residues can also be obtained. The temperature conditions of the reaction of diamine and tetracarboxylic dianhydride, that is, the synthesis reaction of the specific polyamic acid are not particularly limited, for example, in the range of 20°C to 150°C. The reaction time of the synthesis reaction of the specific polyamic acid is, for example, in the range of 10 minutes to 30 hours.
[0085] The organic solvent used in the synthesis of specific polyamic acid is preferably a solvent that can dissolve the tetracarboxylic dianhydride and diamine used, and more preferably a solvent that can dissolve the specific polyamic acid to be generated. As the organic solvent used in the synthesis of specific polyamic acid, from the viewpoint of safety, it is preferably the above-mentioned specific organic solvent. In addition, in the synthesis of specific polyamic acid, it is also possible to use an organic solvent other than the specific organic solvent. Examples of organic solvents other than the specific organic solvent include urea solvents such as tetramethylurea and N,N-dimethylethylurea; sulfoxide solvents such as dimethyl sulfoxide; sulfone solvents such as diphenyl sulfone and tetramethyl sulfone; amide solvents other than the specific organic solvents such as N,N-dimethylacetamide (DMAC), N,N-dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and hexamethylphosphoric triamide; ester solvents such as γ-butyrolactone; halogenated alkyl solvents such as chloroform and dichloromethane; aromatic hydrocarbon solvents such as benzene and toluene; phenol solvents such as phenol and cresol; ketone solvents such as cyclopentanone; and ether solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, and p-cresol methyl ether. These solvents are usually used alone, but two or more of them may be used in combination as needed. In addition, the synthesis reaction of the specific polyamic acid is preferably performed under an inert gas atmosphere such as argon or nitrogen.
[0086] The polyamic acid composition of the present embodiment contains specific polyamic acid and specific organic solvent. In the case of obtaining specific polyamic acid by the above method, the reaction solution (reacted solution) itself can also be used as the polyamic acid composition of the present embodiment. In the case of using the reaction solution itself as the polyamic acid composition of the present embodiment, as the organic solvent for synthesizing specific polyamic acid, it is preferably the above-mentioned specific organic solvent. In addition, the specific polyamic acid of the solid obtained by removing the solvent from the reaction solution can also be dissolved in a specific organic solvent to prepare the polyamic acid composition of the present embodiment.
[0087] The polyamic acid composition of the present embodiment may also include organic solvents other than the specific organic solvent. Wherein, from the viewpoint of safety, the content of the specific organic solvent in the polyamic acid composition of the present embodiment is preferably more than 70 weight %, more preferably more than 80 weight %, and then preferably more than 90 weight %, particularly preferably 100 weight %. It should be noted that the content of the specific polyamic acid in the polyamic acid composition of the present embodiment is not particularly limited, for example, more than 1 weight % and less than 80 weight % relative to the total amount of the polyamic acid composition.
[0088] The weight average molecular weight of specific polyamic acid also depends on its use, preferably 10,000 or more than 1,000,000 or less scope, more preferably 20,000 or more than 500,000 or less scope, and then preferably 30,000 or more than 200,000 or less scope.If the weight average molecular weight is more than 10,000, then it is easy to make coating film or polyimide film (film) by specific polyamic acid or the polyimide obtained using specific polyamic acid.On the other hand, if the weight average molecular weight is less than 1,000,000, then sufficient solubility is shown to solvent, therefore using the following polyamic acid composition, a coating film or polyimide film with smooth surface and uniform thickness can be obtained.The weight average molecular weight used herein refers to the polyethylene oxide conversion value measured using gel permeation chromatography (GPC).
[0089] In addition, as the method for controlling the molecular weight of specific polyamic acid, the method of making any one of acid dianhydride and diamine excessive or the method of quenching the reaction by reacting with monofunctional acid anhydride or amine such as phthalic anhydride or aniline can be exemplified. In the case of making any one of acid dianhydride and diamine excessive for polymerization, if their input molar ratio is between 0.95 and 1.05, the polyimide film with sufficient intensity can be obtained. It should be noted that the above-mentioned input molar ratio is the ratio of the total amount of substance of the diamine used in the synthesis of specific polyamic acid relative to the total amount of substance of the acid dianhydride used in the synthesis of specific polyamic acid (the total amount of substance of diamine / the total amount of substance of acid dianhydride). In addition, by utilizing phthalic anhydride, maleic anhydride, aniline, etc. to carry out end capping, the coloring of the polyimide obtained using specific polyamic acid can also be further reduced.
[0090] In addition, the polyamic acid composition of the present embodiment may contain an imidization accelerator and / or a dehydration catalyst in order to shorten the heating time or develop characteristics.
[0091] The imidization accelerator is not particularly limited, and a tertiary amine can be used. The tertiary amine is preferably a heterocyclic tertiary amine. Preferred specific examples of the heterocyclic tertiary amine include pyridine, picoline, quinoline, isoquinoline, and imidazoles. Preferred specific examples of the dehydration catalyst include acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, and trifluoroacetic anhydride.
[0092] From the viewpoint of shortening the heating time and the viewpoint of showing the characteristics, the amount of the imidization accelerator is preferably 0.1 to 20 parts by weight, more preferably 0.5 to 20 parts by weight, relative to 100 parts by weight of the specific polyamic acid. In addition, from the viewpoint of shortening the heating time and the viewpoint of showing the characteristics, the amount of the dehydration catalyst is preferably 0.1 to 10 parts by weight, more preferably 0.5 to 5 parts by weight, relative to 100 parts by weight of the specific polyamic acid.
[0093] As an imidization accelerator, imidazoles are preferably used. It should be noted that in this specification, imidazoles refer to compounds with 1,3-oxadiazole rings (1,3-oxadiazole ring structures). As imidazoles that can be added to the polyamic acid composition of the present embodiment, there is no particular limitation, for example, 1H-imidazole, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, etc. Among these, 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, more preferably 1,2-dimethylimidazole, 1-benzyl-2-methylimidazole.
[0094] The content of imidazoles is preferably 0.005 mole or more and 0.1 mole or less relative to 1 mole of the amide group of specific polyamic acid, more preferably 0.01 mole or more and 0.08 mole or less, and then preferably 0.015 mole or more and 0.050 mole or less.By containing more than 0.005 mole of imidazoles, it is possible to improve the film strength and transparency of polyimide, by making the content of imidazoles be less than 0.1 mole, it is possible to maintain the storage stability of specific polyamic acid, and improve heat resistance.It should be noted that, in this specification, " the amide group of specific polyamic acid " refers to the amide group generated by the polymerization reaction of diamines and tetracarboxylic dianhydride.
[0095] The mixing method of specific polyamic acid and imidazoles is not particularly limited. From the viewpoint of the ease of controlling the molecular weight of specific polyamic acid, it is preferred to add imidazoles to the specific polyamic acid after polymerization. At this time, imidazoles can be directly added to the specific polyamic acid, or imidazoles can be dissolved in a solvent in advance, and the solution is added to the specific polyamic acid, and the adding method is not particularly limited. It is also possible to add imidazoles to the solution (reacted solution) comprising the specific polyamic acid after polymerization, to prepare the polyamic acid composition of the present embodiment.
[0096] In the polyamic acid composition of the present embodiment, various organic or inorganic low molecular weight compounds or high molecular weight compounds can also be deployed as additives. As additives, for example, plasticizers, antioxidants, dyes, surfactants, leveling agents, silicones, microparticles, sensitizers, etc. can be used. Microparticles include: organic microparticles including polystyrene, polytetrafluoroethylene, etc.; inorganic microparticles including colloidal silicon dioxide, carbon, layered silicates, etc., which can also be porous structures or hollow structures. In addition, the function and form of the microparticles are not particularly limited, for example, they can be pigments, fillers, or fibrous particles.
[0097] In addition, in order to show the appropriate adhesion with the support, the polyamic acid composition of the present embodiment can be made to contain a silane coupling agent. The silane coupling agent can use known silane coupling agents without particular restrictions. In order to show the good adhesion with the support, as an available silane coupling agent, it is preferably a compound containing amino, more preferably selected from the group consisting of 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl diethoxymethyl silane, 3-(ethoxydimethylsilyl) propylamine, N-2-(aminoethyl)-3-aminopropyl trimethoxysilane, N-2-(aminoethyl)-3-aminopropyl methyl dimethoxysilane and N-phenyl-3-aminopropyl trimethoxysilane, and further preferably selected from the group consisting of 3-aminopropyl triethoxysilane and 3-aminopropyl diethoxymethyl silane. One or more compounds, particularly preferably 3-aminopropyl triethoxysilane.
[0098] The mixing ratio of the silane coupling agent to 100 parts by weight of the specific polyamic acid is preferably 0.01 parts by weight or more and 0.50 parts by weight or less, more preferably 0.01 parts by weight or more and 0.30 parts by weight or less, and further preferably 0.01 parts by weight or more and 0.20 parts by weight or less. By making the mixing ratio of the silane coupling agent 0.01 parts by weight or more, the peeling inhibition effect on the support can be fully exerted, and by making the mixing ratio of the silane coupling agent 0.50 parts by weight or less, the molecular weight reduction of the specific polyamic acid can be suppressed, so the embrittlement of the polyimide film can be suppressed.
[0099] In organic solvents with a high pH value such as 3-methoxy-N,N-dimethylpropionamide, the reaction rate of the silane coupling agent may be increased. Since it is difficult to control the condensation reaction of the generated silanol group, it is preferred to reduce the number of alkoxy groups as needed, or use a silane coupling agent with a low reactive alkoxy group. Specifically, by using 3-aminopropyltriethoxysilane, 3-aminopropyldiethoxymethylsilane, 3-(ethoxydimethylsilyl)propylamine, etc., it is possible to control the condensation reaction of the silanol group and achieve good adhesion and peelability with the support.
[0100] The manufacturing method of the polyimide of the present embodiment is equipped with a process of heating the polyamic acid composition of the present embodiment and imidizing a specific polyamic acid. As a method for imidizing a specific polyamic acid, there is no particular restriction, and a known method can be adopted. Below, an example of a method for imidizing a specific polyamic acid is described. Imidization is carried out by dehydrating and ring-closing a specific polyamic acid. The dehydration and ring-closing can be carried out by an azeotropic method, a thermal method or a chemical method using an azeotropic solvent. Alternatively, it is also possible to directly put the polyamic acid composition into a container in which a demoulding treatment such as coating is implemented using a fluorine-based resin, and the polyamic acid composition is heated / dried under reduced pressure, and the dehydration and ring-closing of a specific polyamic acid is carried out. By utilizing the dehydration and ring-closing of the specific polyamic acid carried out by these methods, a polyimide can be obtained. The heating time for each of the above treatments varies depending on the amount of the polyamic acid composition to be dehydrated and the heating temperature, but is generally preferably set within a range of 1 minute to 300 minutes after the treatment temperature reaches the highest temperature.
[0101] In addition, the imidization from a specific polyamic acid to a polyimide can be set to any ratio of more than 1% and less than 100%. That is, a part of the imidized specific polyamic acid can also be synthesized. Especially in the case of imidization by heating, there is a closed-loop reaction from a specific polyamic acid to a polyimide and the hydrolysis of a specific polyamic acid are carried out simultaneously, so that the molecular weight when making a polyimide is lower than the possibility of the molecular weight of a specific polyamic acid, therefore before forming the following polyimide film, it is preferred to imidize a part of the specific polyamic acid in the polyamic acid composition in advance with respect to improving the viewpoint of mechanical properties. In this specification, a part of the imidized polyamic acid is sometimes also referred to as "polyamic acid".
[0102] The manufacturing method of the laminated body of the present embodiment is a manufacturing method of a laminated body having a support and a polyimide film (specifically, a polyimide film containing an imide of a specific polyamic acid). In the manufacturing method of the laminated body of the present embodiment, the specific polyamic acid is heated to dehydrate and close the ring, thereby imidizing. The method for heating the specific polyamic acid is not particularly limited, and for example, the following method can be cited: by coating the polyamic acid composition of the present embodiment on a support, a coating film containing a specific polyamic acid is formed, and the obtained coating film is heat-treated at a temperature of, for example, above 40°C and below 500°C. As a support, examples include: a glass substrate, a metal plate, a PET film (polyethylene terephthalate film), a glass substrate with a sacrificial layer having an amorphous silicon layer (a-Si layer) stacked on a glass substrate, and the like. According to this method, a laminate having a support and a polyimide film (specifically, a polyimide film containing an imide product of a specific polyamic acid) disposed on the support can be obtained.
[0103] The polyimide film (specifically, a polyimide film containing an imide compound of a specific polyamic acid) formed by the manufacturing method of the laminate of the present embodiment is colorless and transparent and has a low yellowness and a glass transition temperature (heat resistance) that can withstand the TFT manufacturing process, so it is suitable for a transparent substrate material for a flexible display. Regarding the content of the polyimide (specifically, the imide compound of a specific polyamic acid) in the above-mentioned polyimide film, relative to the total amount of the polyimide film, for example, 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, and can also be 100% by weight. As components other than polyimide in the polyimide film, for example, the above-mentioned additives (more specifically, microparticles, etc.) can be cited.
[0104] The method for manufacturing an electronic device (more specifically, a flexible device, etc.) of the present embodiment includes: a step Sa of heating the polyamic acid composition of the present embodiment to imidize a specific polyamic acid; and a step Sb of configuring an electronic component on the polyimide film obtained by the step Sa. The step Sa is, for example, the same as the method for manufacturing the laminate of the present embodiment described above. In the step Sb, for example, an electronic component (TFT, etc.) is directly or indirectly configured on the polyimide film obtained by the step Sa.
[0105] When manufacturing electronic devices for flexible displays, first, an inorganic substrate such as glass is used as a support, and a polyimide film is formed thereon. Then, electronic components such as TFTs are arranged (formed) on the polyimide film, thereby forming electronic devices on the support. The process of forming TFTs is usually carried out in a wide temperature range of 150°C to 650°C, but in order to actually achieve the desired performance, an oxide semiconductor layer or a-Si layer is formed at 300°C or above, and depending on the situation, a-Si is sometimes further crystallized using a laser or the like.
[0106] At this time, when the thermal decomposition temperature of the polyimide film is low, exhaust gas may be generated in the process of forming electronic components. The exhaust gas adheres to the oven in the form of sublimates and causes contamination in the oven, or the inorganic film (the barrier film described below, etc.) or the electronic component formed on the polyimide film is peeled off, so the 1% weight reduction temperature of the polyimide is preferably above 500°C. The upper limit of the 1% weight reduction temperature of the polyimide is as high as possible, for example, 600°C. The 1% weight reduction temperature can be adjusted by changing the content of residues with a rigid structure (more specifically, BPDA residues, PDA residues, etc.). To explain in further detail, before forming a TFT, an inorganic film such as a silicon oxide film (SiOx film) or a silicon nitride film (SiNx film) is formed on the polyimide film as a barrier film. At this time, when the heat resistance of the polyimide is low, when imidization is not completely carried out, or when there is a large amount of residual solvent, the polyimide and the inorganic film may be peeled off due to volatile components such as decomposition gas of the polyimide in the high-temperature process after laminating the inorganic film. Therefore, it is desirable that the weight loss rate of the polyimide when isothermally maintained at a temperature in the range of 400°C to 450°C is less than 1%, except that the 1% weight loss temperature of the polyimide is 500°C or more.
[0107] In addition, when the glass transition temperature (Tg) of the polyimide is significantly lower than the process temperature, positional displacement may occur during the formation of the electronic component, so the Tg of the polyimide is preferably above 300°C, more preferably above 350°C, and further preferably above 400°C, and further more preferably above 420°C. The higher the upper limit of the Tg of the polyimide, the more preferred, for example, 470°C. In addition, in general, the thermal expansion coefficient of the glass substrate is smaller than that of the resin, so internal stress will be generated between the glass substrate and the polyimide film. If the internal stress of the glass substrate used as a support or the laminate of the electronic component and the polyimide film is high, the laminate containing the polyimide film will expand during the high-temperature TFT formation process, and then shrink when cooled to room temperature, resulting in problems such as warping or breakage of the glass substrate and peeling of the polyimide film from the glass substrate. Therefore, in the laminate having a support and a polyimide film, the internal stress between the polyimide film and the support is preferably 40 MPa or less, more preferably 30 MPa or less, further preferably 20 MPa, and particularly preferably 10 MPa or less. The lower limit of the internal stress is more preferred, and may be 0 MPa. The internal stress is measured by the same method as in the following embodiment or by a method based on this.
[0108] The polyimide obtained by the manufacturing method of the present embodiment can be well used as a material for display substrates such as TFT substrates and touch panel substrates. When polyimide is used for the above-mentioned purposes, in most cases, after forming an electronic device on a support as described above (in detail, an electronic device with an electronic component formed on a polyimide film), a method of peeling the polyimide film from the support is adopted. In addition, as a material for the support, alkali-free glass is preferably used. Below, an example of a method for manufacturing a laminate of a polyimide film and a support is described in detail.
[0109] First, the polyamic acid composition of the present embodiment is coated (cast) on a support to form a laminate containing a coating film containing a specific polyamic acid and a support containing the coating film. Then, the laminate containing the coating film is heated under conditions such as a temperature of 40°C or more and 200°C or less. The heating time at this time is, for example, 3 minutes or more and 120 minutes or less. It should be noted that a multi-stage heating process may also be provided, such as heating the laminate containing the coating film at a temperature of 50°C for 30 minutes, and then heating it at a temperature of 100°C for 30 minutes. Then, in order to promote the imidization of the specific polyamic acid in the coating film, the laminate containing the coating film is heated under conditions such as a maximum temperature of 200°C or more and 500°C or less. The heating time at this time (heating time at the maximum temperature) is, for example, 1 minute or more and 300 minutes or less. At this time, it is preferred to gradually heat up from a low temperature to a maximum temperature. The heating rate is preferably 2°C / min or more and 10°C / min or less, more preferably 4°C / min or more and 10°C / min or less. In addition, the maximum temperature is preferably in the range of 250°C or more and 480°C or less. If the maximum temperature is above 250°C, imidization is fully carried out, and if the maximum temperature is below 480°C, thermal degradation or coloring of polyimide can be suppressed. In addition, any temperature can be maintained for any time before reaching the maximum temperature. The imidization reaction can be carried out in air, under reduced pressure, or in an inert gas such as nitrogen. In order to show higher transparency, it is preferably carried out in an inert gas such as reduced pressure or nitrogen. In addition, as a heating device, known devices such as a hot air oven, an infrared oven, a vacuum oven, an inert oven, a heating plate, etc. can be used. Through these processes, the specific polyamic acid in the coating film is imidized, and a laminate of a support and a polyimide film (a film containing an imide of a specific polyamic acid) can be obtained.
[0110] The method of peeling the polyimide film from the obtained support and the laminated body of the polyimide film can use a known method. For example, it can be peeled off by hand, or it can be peeled off using a mechanical device such as a driving roller or a robot. Furthermore, a method of arranging a peeling layer between the support and the polyimide film can also be adopted; or a method of forming a silicon oxide film on a substrate having a plurality of grooves, forming a polyimide film with the silicon oxide film as a base layer, and infiltrating the etching solution of silicon oxide between the substrate and the silicon oxide film, and peeling the polyimide film. In addition, a method of separating the polyimide film by irradiating a laser can also be adopted.
[0111] The transparency of the polyimide film can be evaluated by the total light transmittance (TT) according to JIS K7361-1:1997 and the haze according to JIS K7136-2000. When the polyimide film is used for applications requiring high transparency, the total light transmittance of the polyimide film is preferably 75% or more, more preferably 80% or more. In addition, when the polyimide film is used for applications requiring high transparency, the haze of the polyimide film is preferably 1.5% or less, more preferably 1.2% or less, and further preferably 1.0% or less, and may also be 0%. In applications requiring high transparency, the polyimide film is required to have a higher transmittance in the full wavelength region, but the polyimide film has a tendency to easily absorb light on the short wavelength side, and the film itself is often colored yellow. In order to use the polyimide film for applications requiring high transparency, it is preferred to reduce the coloring of the polyimide film. Specifically, in order to use the polyimide film for purposes requiring high transparency, the yellowness (YI) of the polyimide film is preferably less than 25, more preferably less than 20, and may be 0. YI can be measured according to JIS K7373-2006. YI can be adjusted by, for example, changing the content of the residue (1) in a specific polyamic acid. In this way, the polyimide film that is colored and reduced and given transparency is suitable for a transparent substrate for purposes such as replacing glass or a substrate for arranging a sensor or a camera module at the back.
[0112] In addition, there are two types of light extraction methods for flexible displays: a top emission method that extracts light from the front side of the TFT and a bottom emission method that extracts light from the back side of the TFT. The top emission method has the characteristics of being easy to increase the aperture ratio because the light is not blocked by the TFT, and being able to obtain high-definition image quality. The bottom emission method has the characteristics of being easy to align the TFT with the pixel electrode and being easy to manufacture. If the TFT is transparent, the aperture ratio can also be increased in the bottom emission method, so large displays tend to adopt the bottom emission method that is easy to manufacture. The polyimide film obtained by the manufacturing method of this embodiment has a low YI and excellent heat resistance, so it can also be applied to any of the above-mentioned light extraction methods.
[0113] In addition, polyamic acid composition is coated on a support such as a glass substrate, and heated and imidized, so as to form an electronic component, etc., and the polyimide film is peeled off in this batch device manufacturing process, preferably the adhesion between the support and the polyimide film is excellent. So-called adhesion here means close adhesion strength. After the polyimide film on the support forms an electronic component, etc., the polyimide film formed with the electronic component, etc. is peeled off from the support in the manufacturing process, if the polyimide film and the support have excellent adhesion, then the electronic component, etc. can be formed or installed more accurately. In the manufacturing process of configuring the electronic component, etc. at intervals of the polyimide film on the support, from the viewpoint of improving productivity, the peel strength between the support and the polyimide film is preferably more than 0.05N / cm, more preferably more than 0.1N / cm. The determination method of the above-mentioned peel strength is the same method as the following embodiment or the method as a benchmark.
[0114] In the manufacturing process as described above, when the laminate of the polyimide film from the support and the polyimide film is peeled off, the polyimide film from the support can be peeled off by laser irradiation in most cases. In this case, the polyimide film must be made to absorb laser light, so the cut-off wavelength of the polyimide film is required to be longer than the wavelength of the laser used for peeling. The laser peeling uses a XeCl excimer laser with a wavelength of 308nm, so the cut-off wavelength of the polyimide film is preferably more than 312nm, more preferably more than 330nm. On the other hand, if the cut-off wavelength is a long wavelength, the polyimide film will have a trend of being colored yellow, so the cut-off wavelength of the polyimide film is preferably less than 390nm. With regard to the viewpoint of the processability of taking into account transparency (low yellow degree) and laser peeling, the cut-off wavelength of the polyimide film is preferably more than 320nm and less than 390nm, more preferably more than 330nm and less than 380nm. It should be noted that the cutoff wavelength in this specification refers to a wavelength at which the transmittance measured by an ultraviolet-visible spectrophotometer becomes 0.1% or less.
[0115] The polyamic acid composition of the present embodiment and the polyimide obtained by the manufacturing method of the present embodiment can be directly used in the coating or molding process for manufacturing products or components, but can also be used as a material for further coating and other treatments of the formed product formed into a film. In order to be used in the coating or molding process, the polyamic acid composition or polyimide can also be dissolved or dispersed in an organic solvent as needed, and then, as needed, a photocurable component, a thermosetting component, a non-polymerizable binder resin and other components are prepared to prepare a composition containing a specific polyamic acid or polyimide.
[0116] Various inorganic thin films such as metal oxide thin films or transparent electrodes can also be formed on the surface of the polyimide film obtained by the manufacturing method of this embodiment. There is no particular limitation on the film-forming method of these inorganic thin films, and examples thereof include PVD methods such as sputtering, vacuum evaporation, and ion plating, or CVD methods.
[0117] The polyimide film obtained by the manufacture method of the present embodiment has heat resistance, low thermal expansion and transparency, and the internal stress generated when forming a laminate with a glass substrate is also small, and the adhesion with inorganic materials can be ensured in high temperature processes, so it is preferably used in fields and products that can play these characteristics. For example, the polyimide film obtained by the manufacture method of the present embodiment is preferably used for image display devices such as liquid crystal display devices, organic EL, electronic paper, printed matter, color filters, flexible displays, optical films, 3D displays, touch panels, transparent conductive film substrates, solar cells, etc., and then, more preferably used as an alternative material for the part currently using glass. In these uses, the thickness of the polyimide film is, for example, 1 μm or more and 200 μm or less, preferably 5 μm or more and 100 μm or less. The thickness of the polyimide film can be measured using a laser hologram.
[0118] In addition, the polyamic acid composition of the present embodiment can be suitable for the manufacture method of following polyimide film: on a support, apply the polyamic acid composition, heat and carry out imidization, and the polyimide film is peeled off from the support. In addition, the polyamic acid composition of the present embodiment can be suitable for the following batch type device manufacturing procedure: on a support, apply the polyamic acid composition, heat and carry out imidization, after forming electronic components etc. on the formed polyimide film, the polyimide film formed with electronic components etc. is peeled off from the support. Therefore, the manufacture method of the electronic device of the present embodiment can also include the operation of peeling off the polyimide film formed with electronic components etc. from the support.
[0119] Example
[0120] Hereinafter, examples of the present invention will be described, but the scope of the present invention is not limited to the following examples.
[0121] <Measurement and evaluation methods of physical properties>
[0122] First, the measurement method and evaluation method of the physical properties of polyimide (polyimide film) are described.
[0123] [Internal stress]
[0124] On a glass substrate (trade name: Eagle XG, material: alkali-free glass, thickness: 0.7mm, size: 100mm×100mm) manufactured by Corning, the amount of warpage was measured in advance, and each polyamic acid composition prepared in the following embodiments and comparative examples was applied by a spin coater, and heated at 120°C for 30 minutes in air, and then heated at 460°C for 45 minutes under a nitrogen atmosphere to obtain a laminate having a polyimide film with a thickness of 10μm on a glass substrate. In order to eliminate the influence of water absorption by the polyimide film, the laminate was dried at 120°C for 10 minutes, and then the warpage of the laminate under a nitrogen atmosphere at a temperature of 25°C was measured using a thin film stress measuring device ("FLX-2320-S" manufactured by KLA-Tencor). Then, according to the warpage of the glass substrate before the polyimide film is formed and the warpage of the laminate, the internal stress generated between the glass substrate and the polyimide film is calculated using the Stoney formula. When the internal stress was 30 MPa or less, it was evaluated as “the internal stress can be reduced.” On the other hand, when the internal stress exceeded 30 MPa, it was evaluated as “the internal stress cannot be reduced.”
[0125] [1% weight loss temperature (TD1)]
[0126] A polyimide film sampled from each laminate obtained in the following examples and comparative examples (specifically, a polyimide film sampled in a manner to make the weight 10 mg) was used as a measurement sample. A differential thermal-thermogravimetric simultaneous measurement apparatus ("TG / DTA7200" manufactured by Hitachi High-Tech Science Co., Ltd.) was used. The temperature was raised from 25°C to 650°C at 20°C / min under a nitrogen atmosphere. The weight of the sample at a measurement temperature of 150°C was used as a reference, and the measurement temperature when the weight was reduced by 1% by weight relative to the reference was taken as the 1% weight loss temperature (TD1).
[0127] [Film-forming properties]
[0128] (Film forming properties on glass substrate)
[0129] Each polyamic acid composition prepared in the following examples and comparative examples was applied to a glass substrate (trade name: Eagle XG, material: alkali-free glass, thickness: 0.7 mm, size: 100 mm×100 mm) manufactured by Corning Incorporated using a spin coater, and heated at 120° C. for 30 minutes in air, and then heated at 460° C. for 45 minutes in a nitrogen atmosphere to obtain a laminate having a polyimide film having a thickness of 10 μm on the glass substrate. The obtained laminate was visually confirmed to be floating between the glass substrate and the polyimide film.
[0130] (Film Formability on a-Si Layer)
[0131] After stacking a-Si layer (thickness: 100nm) on a glass substrate (trade name: Eagle XG, material: alkali-free glass, thickness: 0.7mm, size: 100mm×100mm) manufactured by Corning, each polyamic acid composition prepared in the following embodiments and comparative examples is applied on the a-Si layer by a spin coater. Then, the substrate coated with the polyamic acid composition is heated in air at 120°C for 30 minutes, and then heated at 460°C for 45 minutes under a nitrogen atmosphere to obtain a laminate having an a-Si layer and a polyimide film having a thickness of 10μm in sequence on a glass substrate. The obtained laminate is visually confirmed to have floating between the a-Si layer and the polyimide film.
[0132] (Evaluation criteria for film forming properties)
[0133] When there was no floating between the glass substrate and the polyimide film and between the a-Si layer and the polyimide film, it was evaluated as "the occurrence of poor adhesion was suppressed and the film forming property was good". On the other hand, when there was floating between at least one of the glass substrate and the polyimide film and between the a-Si layer and the polyimide film, it was evaluated as "the occurrence of poor adhesion was not suppressed and the film forming property was not good".
[0134] [Peel strength]
[0135] For the polyimide films of each laminate obtained in the following embodiments and comparative examples, a slit with a width of 10 mm was cut using a cutter in accordance with ASTM D1876-01 standard, and a tensile testing machine ("Strograph VES1D" manufactured by Toyo Seiki Co., Ltd.) was used to peel the polyimide film 50 mm from the glass substrate at a tension rate of 50 mm / min and a peeling angle of 90° under an environment of temperature 23°C and humidity 55% RH. The average value of the peel strength at this time was taken as the peel strength.
[0136] <Production of polyimide film>
[0137] The following is a description of the method for preparing the polyimide film (laminated body) of the examples and comparative examples. It should be noted that the following abbreviations are used to describe the compounds and reagents. In addition, the preparation of the polyamic acid composition used in the preparation of the polyimide film was carried out under a nitrogen atmosphere.
[0138] MPA: 3-methoxy-N,N-dimethylpropionamide
[0139] NBP: 1-Butyl-2-pyrrolidone
[0140] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0141] BPAF: 9,9-bis(3,4-dicarboxyphenyl)fluorene anhydride
[0142] SFDA: Spiro[11H-difuro[3,4-b:3',4'-i]xanthene-11,9'-[9H]fluorene]-1,3,7,9-tetraone
[0143] PDA: p-phenylenediamine
[0144] BAFL: 9,9-bis(4-aminophenyl)fluorene
[0145] PAM-E: 1,3-bis(3-aminopropyl)tetramethyldisiloxane
[0146] ODA: 4,4'-oxydiphenylamine
[0147] APS: 3-aminopropyltriethoxysilane
[0148] APDE: 3-aminopropyldiethoxymethylsilane
[0149] [Example 1]
[0150] To a 300 mL glass separable flask equipped with a stirrer with a stainless steel stirring rod and a nitrogen inlet tube, 85.0 g of MPA was added as an organic solvent for polymerization. Then, while stirring the contents of the flask, 4.037 g of PDA was added to the flask for dissolution. Then, after adding 0.171 g of BPAF and 10.792 g of BPDA to the contents of the flask, the contents of the flask were stirred for 6 hours at a temperature of 25 ° C. Then, after adding 0.005 g of APS to the contents of the flask, the contents of the flask were further stirred for 6 hours at a temperature of 25 ° C to obtain a polyamic acid composition. The obtained polyamic acid composition was coated on a glass substrate manufactured by Corning Incorporated (trade name: Eagle XG, material: alkali-free glass, thickness: 0.7 mm, size: 100 mm×100 mm) using a spin coater, and heated at 120° C. for 30 minutes in air, and then heated at 460° C. for 45 minutes in a nitrogen atmosphere to obtain a laminate having a polyimide film with a thickness of 10 μm on the glass substrate (the laminate of Example 1).
[0151] [Examples 2 to 21 and Comparative Examples 1 to 7]
[0152] Except that the acid dianhydride used and its input ratio, the diamine used and its input ratio, the silane coupling agent used and its addition amount, and the type of solvent are as shown in Table 1 and Table 2, the laminates of Examples 2 to 21 and Comparative Examples 1 to 7 are obtained by the same method as in Example 1. It should be noted that in Examples 2 to 4, 9 to 14, 17, 19 and 21, and Comparative Examples 1, 3 and 5 to 7 in which no silane coupling agent is used, after all the acid dianhydride is added to the flask, the contents of the flask are stirred for 6 hours under an environment of a temperature of 25°C to obtain a polyamic acid composition. In addition, for any one of Examples 2 to 21 and Comparative Examples 1 to 7, the total amount of acid dianhydride when preparing the polyamic acid composition is the same as that in Example 1. In addition, for any one of Examples 2 to 21 and Comparative Examples 1 to 7, the total amount of diamine when preparing the polyamic acid composition is the same as that in Example 1.
[0153] Regarding Examples 1 to 21 and Comparative Examples 1 to 7, the acid dianhydride, diamine, silane coupling agent and solvent used, as well as internal stress, TD1, film forming properties and peel strength are shown in Tables 1 and 2. It should be noted that in Tables 1 and 2, the "-" in the columns of acid dianhydride, diamine and silane coupling agent means that the component was not used. In addition, in Tables 1 and 2, the "-" in the column of peel strength means that the peel strength was not measured.
[0154] In addition, in Tables 1 and 2, the values in the column of "acid dianhydride" are the content of each acid dianhydride relative to the total amount of diamines used (100 mol%) (unit: mol%). In addition, in Tables 1 and 2, the values in the column of "diamine" are the content of each diamine relative to the total amount of diamines used (100 mol%) (unit: mol%). In addition, in Tables 1 and 2, the values in the column of "silane coupling agent" are the addition amount of silane coupling agent relative to 100 parts by weight of polyamic acid (unit: parts by weight). In addition, with respect to any one of Examples 1 to 21 and Comparative Examples 1 to 7, the mole fraction of each residue of polyamic acid in the prepared polyamic acid composition is consistent with the mole fraction of each monomer (diamine and tetracarboxylic dianhydride) used in the synthesis of polyamic acid.
[0155] [Table 1]
[0156]
[0157] [Table 2]
[0158]
[0159] The polyamic acid in the polyamic acid composition used in Examples 1 to 21 has a residue (1), a BPDA residue, and a PDA residue. The polyamic acid composition used in Examples 1 to 21 contains a specific organic solvent.
[0160] As shown in Tables 1 and 2, in Examples 1 to 21, the internal stress was 30 MPa or less. Therefore, in Examples 1 to 21, the internal stress can be reduced. In Examples 1 to 21, there is no floating between the glass substrate and the polyimide film, and between the a-Si layer and the polyimide film. Therefore, in Examples 1 to 21, the occurrence of poor adhesion is suppressed, and the film forming property is good.
[0161] The polyamic acid in the polyamic acid composition used in Comparative Examples 1 to 7 has a BPDA residue and a PDA residue, but does not have a residue (1). The polyamic acid composition used in Comparative Examples 1 to 7 contains a specific organic solvent.
[0162] As shown in Table 2, in Comparative Examples 1 to 6, there was floating between the glass substrate and the polyimide film, and between the a-Si layer and the polyimide film. Therefore, in Comparative Examples 1 to 6, the occurrence of poor adhesion was not suppressed, and the film forming property was not good. In Comparative Example 7, the internal stress exceeded 30 MPa. Therefore, in Comparative Example 7, the internal stress could not be reduced.
[0163] The above results show that according to the present invention, it is possible to use a highly safe solvent, suppress the occurrence of poor adhesion, and reduce internal stress.
Claims
1. A polyamic acid composition comprising polyamic acid and an organic solvent, The polyamic acid comprises a residue of a divalent organic group represented by the following chemical formula (1), a 3,3',4,4'-biphenyltetracarboxylic dianhydride residue, and a p-phenylenediamine residue. The organic solvent comprises one or more compounds selected from the group consisting of compounds represented by the following general formula (2) and compounds represented by the following general formula (3), In the general formula (2), R 1 , R 2 and R 3 Each independently represents a hydrogen atom or a monovalent organic group having 1 or more carbon atoms, and R 1 , R 2 and R 3 At least one of represents a monovalent organic group having 2 or more carbon atoms, In the general formula (3), R 4 It represents a monovalent organic group having 2 or more carbon atoms.
2. The polyamic acid composition according to claim 1, wherein The residue containing the divalent organic group represented by the chemical formula (1) is one or more residues selected from the group consisting of a tetravalent organic group represented by the following chemical formula (4), a tetravalent organic group represented by the following chemical formula (5), and a divalent organic group represented by the following chemical formula (6), 3. The polyamic acid composition according to claim 1, wherein The content of the residue containing the divalent organic group represented by the chemical formula (1) is 15 mol% or less relative to 100 mol% of the total of all tetracarboxylic dianhydride residues and all diamine residues constituting the polyamic acid.
4. The polyamic acid composition according to claim 1, wherein The organic solvent is 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide or 1-butyl-2-pyrrolidone.
5. The polyamic acid composition according to claim 1, wherein The polyamic acid further has a 1,3-bis(3-aminopropyl)tetramethyldisiloxane residue.
6. The polyamic acid composition according to claim 5, wherein The content of the 1,3-bis(3-aminopropyl)tetramethyldisiloxane residue is 0.1 mol % or more and 1.0 mol % or less relative to the total amount of the diamine residues constituting the polyamic acid. The polyamic acid composition according to claim 1 , further comprising a silane coupling agent.
8. A method for producing a polyimide, wherein: The polyamic acid composition according to claim 1 is heated to imidize the polyamic acid.
9. A method for producing a laminate comprising a support and a polyimide film, In the production method, the polyamic acid composition according to claim 1 is applied onto a support to form a coating film containing the polyamic acid, and the coating film is heated to imidize the polyamic acid.
10. A method for manufacturing an electronic device, comprising: Step Sa, heating the polyamic acid composition according to claim 1 to imidize the polyamic acid; and The step Sb is to arrange electronic components on the polyimide film obtained in the step Sa.
Citation Information
Patent Citations
Polyimide precursor aqueous solution composition
JP2012036382A
New solvents for polyamide-imide and polyimide
JP2017517582A
Solvent for resin synthesis and method for producing synthetic resin using said solvent
WO2022054850A1